T1 Mapping in Ischemic Heart Disease - Dall'Armellina, E; Ferreira, V; Neubauer, S (Current Medicine Group LLC 1, 2014)
The major advantage of T1 mapping techniques lies in the quantitative assessment of the tissue composition on a voxel by voxel basis. Both native and postcontrast T1 mapping, including extracellular volume (ECV) mapping, are promising cardiovascular magnetic resonance (CMR) imaging techniques, which may provide more insight into the clinical meaning of myocardial injury in acute coronary syndromes, and into the relationship between extracellular volume and long term LV remodeling. Native T1 mapping has been shown to allow depiction of edema and myocardial area at risk with greater sensitivity than any other standard imaging technique such as T2 weighted imaging. ECV mapping is very promising for the assessment of extracellular volume as validated with histologic sample of collagen fraction. However, only few studies have been published so far. These methods may become a cornerstone for the clinical applications of quantitative mapping techniques for myocardial tissue characterization, with on-going efforts toward further validation and standardization. © 2014 Springer Science+Business Media New York.